The Validation of a Simple, Robust, Stability-Indicating RP-HPLC Method for the Simultaneous Detection of Lamivudine, Tenofovir Disoproxil Fumarate, and Dolutegravir Sodium in Bulk Material and Pharmaceutical Formulations. (4th February 2022) - Omoteso, Omobolanle Ayoyinka; Milne, Marnus; Aucamp, Marique
Abstract : An effective analytical method is requisite to ensure the accurate identification and quantification of drug(s), either in bulk material or in complex matrices, which form part of finished pharmaceutical products. For the purpose of a pharmaceutical formulation study, it became necessary to have a simple, yet robust and reproducible reversed-phase HPLC method for the simultaneous detection and quantification of lamivudine (3TC), tenofovir disoproxil fumarate (TDF), and dolutegravir sodium (DTG) in bulk form, complex polymeric matrices, and during drug release studies. A suitable method was developed using a Kinetex® C18, 250 × 4.6 mm column as stationary phase and a mobile phase consisting of 50 : 50 v/v methanol and water with 1 mL orthophosphoric acid, with a flow rate of 1.0 mL/min and column temperature maintained at 35°C. A detection wavelength of 260 nm and an injection volume of 10 μ L were used. The method was validated according to the International Conference on Harmonization (ICH) guideline Q2 (R1 ), and the parameters of linearity and range, accuracy, precision, specificity, limit of detection (LOD), limit of quantification (LOQ), robustness, and stability were all determined. Acceptable correlation coefficients for linearity (R2 ) of >0.998 for each of the three drugs were obtained. The LOD was quantified to be 56.31 μ g/mL, 40.27 μ g/mL, and 7.00 μ g/mL for 3TC, TDF, and DTG, respectively, and the LOQ was quantified as 187.69 μ g/mL, 134.22 μ g/mL, and 22.5 μ g/mL for 3TC, TDF, and DTG, respectively. In relation to all the determined validation parameters, this method proves to be suitable for the accurate identification and quantification of the three ARVs, either alone or in combination, as well as when incorporated into polymeric matrices. Furthermore, the method proves to be suitable to detect degradation of the compounds.